Giant odontogenic fibroma of maxilla - Baser, Brajendra (Ann Maxillofac Surg, 2014)
Odontogenic fibroma is a benign ectomesenchymal tumor classified as central and peripheral on the basis of its location and as an epithelium rich or epithelium poor based on its histological features. Radiological findings consist of radiolucent areas with well-defined bony margins. The lesion is detected early because of its location and usually treated with surgical excision and curettage. We present a case of giant odontogenic fibroma of right maxilla presenting as gross facial deformity and posing a dual challenge of excising the tumor mass and reconstructing the ensuing defect.